Ebersole and Hess' toward healthy aging : human needs and nursing response - Touhy, Theris A.; Jett, Kathleen F. (London, United Kingdom : Elsevier Health Sciences, 2012)
Grounded in the core competencies recommended by the AACN in collaboration with the Hartford Institute for Geriatric Nursing, Ebersole & Hess' Toward Healthy Aging, 8th Edition is the most comprehensive resource on health promotion and maintenance for older adults and their caregivers. With coverage of communication, safety and ethical considerations, new genetic research, key aging issues, and common and uncommon conditions, you will have the knowledge you need to promote healthy lifestyle choices, properly address end-of-life issues, and provide effective, holistic care for older adults
Part 1 Foundations of healthy aging -- Part 2 Foundations of caring -- Part 3 Wellness and function -- Part 4 Wellness and chronic illness -- Part 5 Healthy aging for elders and their families
Includes bibliographical references and index.
Keywords: GERIATRIC NURSING